The Effectiveness Of Problem-Based Learning (PBL) And Project-Based Learning (PJBL) Learning Models On Disaster Mitigation Materials On Learning Motivation Of Xi Social Studies Class - Husyain Rifai, Muh (International Journal of Educational Research & Social Sciences, 2023)
The purpose of this research is (1) Researchers want to know the learning motivation of students in disaster mitigation material if using the PBL model,(2) Researchers want to know the learning motivation of students in disaster mitigation material if using the PJBL model. This research method uses quantitative methods with a quasi-experimental approach. This research was conducted in two classes, namely class XI IPS 2 as the first experimental group with a project-based learning method (PBL) and class XI IPS 3 as the second experimental group with a problem-based learning method (PBL). The analysis used is the MANOVA analysis technique, which is a multivariate analysis to test stimulate differences between two or more dependent variables. The results of this study are: (1) the PjBL learning model is effectively used in the first experimental class (2) the PBL learning model is effectively used in the second experimental class.